South African foreign policy review. - Landsberg, Chris; Van Wyk, Jo-Ansie (Africa Institute of South Africa, 2012)
The richness of public and academic discourses on the past, present, and future direction of South Africa's role in Africa and the world suggests that as a sub-discipline of politics, South African foreign policy is ready for a systematic and regular appraisal in the form of a series of publications that the Institute for Global Dialogue will call South African Foreign Policy Review. This is also because constant changes in international and domestic circumstances impinge on the management and analysis of South Africa's foreign policy. This, the first review, provides an important opportunity to build on existing foreign policy works in order to take stock of the road already travelled in the past decade or so. This is crucial in laying some basis for anticipating the country's future role, and considering the opportunities and challenges, which future volumes of the review will consider. This volume provides a wide-ranging appraisal of the relationship between stated foreign policy goals and actual outputs and outcomes, an assessment of how foreign policy has actually been operationalized and implemented. To this end, common themes in South African foreign policy provide the framework for this first review. These include foreign policy decision-making; soft power dynamics in the foreign policy's strategic calculus; diplomatic tools used, economic diplomacy, peace diplomacy and paradiplomacy; South Africa's relations with key states in Africa, in the global south and in the global north; South Africa's approach to Africa multilateral, global multilateralism/governance. The review hopes to stimulate further discussion and thinking on the challenges confronted, and the future shape and direction of South Africa's foreign policy.